Family productive strategies, perceptions and deforestation in a context of forest transition: the case of Tena in the Ecuadorian Amazon - Anda Basabe, Susana (2017)
This article explains how the family productive strategies of farmer settlers and their perceptions of the forest influence the rate of deforestation. This particular approach, based on the analysis of endogenous processes, seeks to contextualize and understand how farmers operate within a context of «forest transition», as a result of significant economic changes, market expansion and road infrastructuredevelopment. Our central argument is that the farmers’ strategies in Tena, in relation to the rate of deforestation on their farms, are a result of the combination of a set of economic processes of survival in the short and medium term and of their mental or cultural perceptions of the forest. Such endogenous processes arenot only responses to external contexts but are also derived from demographic cycles and accumulation dynamics that occur within the families of producers.